Biodistribution and tolerance of intravenous iodine‐131‐labelled hypericin in healthy dogs. (4th January 2018) - Abma, E.; Peremans, K.; De Vos, F.; Bosmans, T.; Kitshoff, A. M.; Daminet, S.; Ni, Y.; Dockx, R.; de Rooster, H.
Abstract : Hypericin (Hyp) is a necrosis‐avid compound that can be efficiently labelled with radioiodine for both diagnostic and therapeutic purposes. Before 131 I‐Hyp can be considered as a clinically useful drug in a combination therapy for canine cancer patients, evaluation of its toxicity is necessary. The aim of this study was to investigate the biodistribution and tolerance of a single dose administration of 131 I‐Hyp. Three healthy dogs were included. 131 I‐Hyp at a dose of 0.2 mg/kg and an activity of 185 MBq was intravenously injected. The effects on physical, haematological and biochemical parameters were characterized and the biodistribution and elimination pattern, the effective half‐life and dose rate were assessed. Drug‐related adverse events were limited to mild gastrointestinal signs, resolving within 48 hours. No significant differences were found in blood haematology and serum biochemistry before and after treatment. Following administration, highest percentage of injected dose (%ID ± SD) was found in the liver (5.5 ± 0.33), the lungs (4.17 ± 0.14) and the heart (3.11 ± 0.78). After 24 hours, highest %ID was found in colon (4.25 ± 1.45) and liver (3.45 ± 0.60). Clearance from all organs was effective within 7 days. Effective half‐life was established at 80 hours, and the dose rate fell below <20 μSv/h at 1 m within 1 day. The current study reveals that single dose treatment with 131 I‐Hyp at the described dose is well tolerated by healthy dogs and supports the use of radioiodinated hypericin in a combination therapy for canine cancer patients.